Carbonized Polymer Dots Enhancing Interface Stability of LiNi0.8Co0.1Mn0.1O2 Cathodes - Lin Li; Yaojian Zhang; Naifang Hu; Kejian Wang; Yuehui Liu; Xiaogang Wang; Xinhong Zhou; Jun Ma; Guanglei Cui (Advanced Materials Interfaces, 2023)
Abstract The high energy density, low cost, and low toxicity of LiNi0.8Co0.1Mn0.1O2 (NCM811) cathodes has led to their large‐scale mass production. However, the poor interfacial stability between NCM811 and organic electrolytes impairs the long‐cycle performance of lithium ions batteries. In this study, carbonized polymer dots (CPDs) are successfully introduced onto the surface of NCM811 (NCM811@CPDs) via a simple physical mixing process. CPDs with rich surface oxygen functional groups form strong covalent bonds with transition metal (TM) ions at the NCM811 surface, distinctly restraining surface structure degradation, and transition metal ion dissolution. Furthermore, CPDs facilitate the formation of a compact and steady cathode electrolyte interface (CEI) layer during electrochemical cycling. As a result, the NCM811@1 wt% CPDs exhibit enhanced cycling performance with a capacity retention of 89.77% after 100 cycles at 0.5 C compared to 55.39% of the bare NCM811. This facile and effective surface decoration strategy provides valuable guidance for improving the stability and cycling performance of Ni‐rich cathodes.